Impact of Roman Law on the European Convention on Human Rights - Pashuk, Taras (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article is dedicated to the analysis of the impact of Roman law on the modern system of human rights protection, established by the European Convention on Human Rights. The impact of Roman law on the contemporary legal thinking and reasoning in this area is analysed with regard to the proceedings stipulated by the Convention. An argument is made that certain important rules of the Convention procedure have been affected by Roman-law principles. Then analysis is made with regard to the substance of human rights standards under the Convention. In examining these issues, reference is made to the case-law of the European Court of Human Rights. It is in the practical application of the Convention that the real effect of the Roman-law concepts and doctrines becomes visible and can be appreciated.

Artykuł jest poświęcony analizie wpływu prawa rzymskiego na współczesny system ochrony praw człowieka, stanowiony przez Europejską Konwencję Praw Człowieka. Wpływ prawa rzymskiego na teraźniejsze myślenie prawne i argumentację prawniczą w tym obszarze jest zbadany przez pryzmat postępowania ustalonego według Konwencji. Uzasadniono, że powstanie niektórych ważnych reguł postępowania konwencyjnego zostało zapoczątkowane przez zasady prawa rzymskiego. Badanie zostało prowadzone na kanwie treści standardów praw człowieka, zawartych w Konwencji. Ważne miejsce w studium zajmuje analiza spraw rozstrzygniętych przez Europejski Trybunał Praw Człowieka. Faktyczny wpływ pojęć i koncepcji prawa rzymskiego staje się najbardziej widoczny i może być udowodniony właśnie poprzez badanie praktyki stosowania Konwencji.
Keywords: Roman law; legal principles; European Convention on Human Rights; European Court of Human Rights; prawo rzymskie; zasady prawne; Europejska Konwencja Praw Człowieka; Europejski Trybunał Praw Człowieka